2014
DOI: 10.4049/jimmunol.1302490
|View full text |Cite
|
Sign up to set email alerts
|

Cross-Dressing by Donor Dendritic Cells after Allogeneic Bone Marrow Transplantation Contributes to Formation of the Immunological Synapse and Maximizes Responses to Indirectly Presented Antigen

Abstract: The stimulation of naive donor T cells by recipient alloantigen is central to the pathogenesis of graft-versus-host disease after bone marrow transplantation (BMT). Using mouse models of transplantation, we have observed that donor cells become “cross-dressed” in very high levels of recipient hematopoietic cell–derived MHC class I and II molecules following BMT. Recipient-type MHC is transiently present on donor dendritic cells (DCs) after BMT in the setting of myeloablative conditioning but is persistent afte… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
36
1

Year Published

2015
2015
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 33 publications
(38 citation statements)
references
References 29 publications
1
36
1
Order By: Relevance
“…Trogocytosis may hold particular relevance for transplantation, because the ability to transfer allogeneic membrane proteins between donor and recipient immune cells is likely to have more profound consequences than transfer of self-proteins. Nevertheless, few studies have reported functional significance for either solid organ or hematopoietic stem cell transplantation (26,27) and our findings thus emphasize the potentially important contribution of trogocytosis in initiating adaptive alloimmunity.…”
Section: Discussionmentioning
confidence: 59%
“…Trogocytosis may hold particular relevance for transplantation, because the ability to transfer allogeneic membrane proteins between donor and recipient immune cells is likely to have more profound consequences than transfer of self-proteins. Nevertheless, few studies have reported functional significance for either solid organ or hematopoietic stem cell transplantation (26,27) and our findings thus emphasize the potentially important contribution of trogocytosis in initiating adaptive alloimmunity.…”
Section: Discussionmentioning
confidence: 59%
“…Imaging flow cytometry has successfully been used to quantify colocalization of proteins [2,20,27,31]. We chose to use imaging flow cytometry since it provides a unique tool to quantify colocalization in a large number of cells and is perfectly adapted to screen multiple clones.…”
Section: Resultsmentioning
confidence: 99%
“…To avoid possible effects of the trypsin and/or EDTA on distribution of the receptor, cells were re-suspended mechanically. Our group has successfully applied this technique to assess HEK293 by regular flow cytometry [27]. Cells were then stained with an anti-HA mouse IgG1 monoclonal antibody conjugated with Alexa Fluor 488 (Cell Signaling, catalog # 2350S) together with an anti-c-Myc mouse IgG1 monoclonal antibody conjugated with Alexa Fluor 647 (Cell Signaling, catalog # 2233S) (1:25 dilution for 1 hour at room temperature).…”
Section: Methodsmentioning
confidence: 99%
“…Activation of the latter by host DCs is possible if DCs were ‘cross-dressed' with intact donor MHC molecules in the graft. Although not formally shown here, cross-dressing has been described in vitro and in vivo and likely participates in immune responses to viruses, bone marrow transplants and organ transplants1736373839. Therefore, host DCs that replace donor DCs in the graft are not limited to engaging indirectly alloreactive T cells, which represent a minute fraction of the host's alloreactive T-cell repertoire, but can also present non-self MHC molecules to the much larger population of directly alloreactive T cells.…”
Section: Discussionmentioning
confidence: 96%